Innovative Budgeting Strategies in the Digital Era: Leveraging ERP Systems for Enhanced Financial Control - Lipelis, Mikhail (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
The digital era has been very efficient in changing how to manage finances where Enterprise resource planning systems are good examples of improving the efficiency of budgeting and financial control. The purpose of this study is to analyze effect of Enterprise resource planning adoption on key financial performance indicators, namely reduction of unplanned expense, reduction of budget variance, budget adherence and accuracy of financial reporting amongst five countries: United States, United Kingdom, Germany, Poland and China. An econometric analysis, using Enterprise resource planning with panel data on fixed effects regression and difference in differences models during the period of 2020—2024 has been carried out to determine Enterprise resource planning effectiveness. The author found that Enterprise resource planning adoption has a significant effect on financial control, but this effect depends on the country and the degree to which the country’s economic conditions as well as digital maturity levels support adoption. In the role of the enterprise resource planning systems in modern financial management the study presents empirical insights and proposes strategic recommendations on the optimization of budgeting processes.